Innovation of Junior High School English Layered Teaching with Artificial Intelligence–Exploration of Classroom Transformation Based on Difference Education Concept - Nie, Hui (International Journal of Advanced AI Applications, 2025)
Facing the demand of junior high school English teaching transforming from "knowledge-based" to "literacy-oriented" under the background of new curriculum reform, the contradiction between the traditional homogeneous teaching mode and students' individualized development has become increasingly prominent. Based on the theory of differential education, this study integrates artificial intelligence technology to construct an innovative system of junior high school English hierarchical teaching, aiming at solving the dilemma of "pseudo-hierarchical" and realizing the organic unity of large-scale education and personalized training. Under the background of new curriculum reform and educational informatization, the traditional "one size fits all" teaching mode is difficult to meet the individual development needs of students, and artificial intelligence technology provides support for solving this dilemma. This paper expounds the concept of differential education, constructs a closed-loop model of "data diagnosis-intelligent stratification-dynamic intervention-accurate evaluation", and innovates the stratified teaching paradigm of junior high school English. Through multi-modal data fusion, the portrait of learning situation is constructed, the improved clustering algorithm is used to realize dynamic grouping, the intelligent resource recommendation engine is built to meet individual needs, the human-machine collaborative hybrid education and teaching mode is formed, and the evaluation system is improved by blockchain technology innovation, aiming at providing solutions for personalized training in large-scale education, helping the reform of basic education curriculum and the construction of intelligent education ecology, comprehensively promoting the balanced development of education and promoting the improvement of education level.